Frequent expression of smooth muscle markers in malignant fibrous histiocytoma of bone. Issue 11 (1st November 2002) - Ueda, T; Araki, N; Mano, M; Myoui, A; Joyama, S; Ishiguro, S; Yamamura, H; Takahashi, K; Kudawara, I; Yoshikawa, H
Abstract : Background/Aims: Malignant fibrous histiocytoma (MFH) of bone, a relatively rare primary malignant bone tumour, is a distinct clinicopathological entity as opposed to MFH derived from soft tissue. Although the true histogenesis of this condition is still controversial, a considerable number of cases of MFH in soft tissue show positive immunohistochemical reactivity for muscle markers such as desmin, common muscle actin (HHF35), and α smooth muscle actin (SMA), suggesting that MFH cells are myofibroblastic in nature. Methods: This study investigated immunoreactivity for several different muscle markers in 19 cases of MFH of bone together with reverse transcription polymerase chain reaction (RT-PCR) analysis on frozen tissue samples that were available in four cases, and compared the data with those found in 11 cases of osteosarcoma and 11 cases of soft tissue MFH treated over the same period. Results: Immunohistochemistry revealed that MFH of bone showed relatively frequent expression of smooth muscle markers, including calponin (nine cases), α-SMA (nine cases), and SM22α (18 cases), and this was confirmed by RT-PCR analysis. However, only one, two, and three cases of MFH of bone showed positive staining for desmin, MyoD1, and HHF35, respectively. Similarly, 11 osteosarcoma cases were relatively frequently positive for α-SMA (five cases), calponin (four cases), and SM22α (seven cases), and less frequently positive for desmin (one case), MyoD1 (none), and HHF35 (none). In contrast, very few MFH of soft tissue cases (n = 11) showed positive reactivity for all of these muscle markers. It has recently been reported that human bone marrow stromal cells also express various kinds of smooth muscle markers including α-SMA and calponin. Conclusions: These results suggested that MFH of bone may derive from mesenchymal stromal cells in bone marrow and has a more myofibroblastic differentiation than soft tissue MFH.